Current state of research on acupuncture for the treatment of post-stroke dysphagia: a scoping review - Guo, Haoran; Pan, Xingfang; Zheng, Yujie; Yang, Xue; Xu, Hanyu; Zhang, Yuan; Sun, Yuqi; Wang, Zeran; Ba, Te; Pang, Bo; Hao, Ting; Zhang, Junhua; et al. (Frontiers in Neuroscience, 2024)
Objective Post-stroke dysphagia (PSD) is a common complication of stroke. Acupuncture as one of the traditional therapies in traditional Chinese medicine (TCM), can change the excitability of cerebral cortical nerve cells, and promote the recovery of neurological and swallowing functions. Several clinical primary studies (including RCTs, cohort studies, etc.) and systematic reviews have demonstrated its efficacy and safety in patients with PSD. The positive effects of acupuncture on PSD are also mentioned in international clinical and treatment guidelines, while there is no synthesis of this evidence. This scoping review aims to summarize the evidence from clinical primary studies, reviews, systematic reviews, and guidelines on acupuncture for the treatment of PSD and explore the breadth of this evidence, provide an overview of the range and characteristics of existing evidence, research gaps, and future research priorities in treating PSD with acupuncture. Method PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, SinoMed, Wan Fang Data, and VIP databases were searched from inception until June 12, 2024. The relevant data were presented through bubble diagrams, line graphs, and structured tables along with descriptive statistics and analysis. This scoping review was conducted based on the PRISMA-ScR Checklist. Results A total of 1,130 studies were included. Most of the studies were conducted in China, with the number increasing over time. The studies included 254 reviews, 815 clinical studies (678 RCTs,107 nRCTs, 12 case reports, 14 cohort studies, and four case series), 51 systematic reviews, and 10 guidelines. Acupuncture interventions included manual acupuncture (MA), electroacupuncture (EA), and MA/EA combined with acupuncture-related methods (such as scalp acupuncture, auricular acupuncture, warm acupuncture, etc.). The most frequently used acupoint was RN23. Acupuncture is often applied in combination with other treatments, such as herbal medicine, Western medicine, rehabilitation training, swallowing training, or catheter balloon dilatation. Effective rates and WTS were the most frequently used outcomes. Most studies reported significant efficacy and only a few studies explicitly reported adverse events. Acupuncture received positive recommendations in nine guidelines for the treatment of PSD. Conclusion As a convenient and safe traditional Chinese medicine therapy with its characteristics, acupuncture can improve different stages and types of dysphagia without causing serious adverse reactions. In the future, more standardized international cooperative clinical research is needed to identify the influence of different acupuncture intervention times on the curative effect and dose-effect relationship of acupuncture; standardize the clinical acupoint selection scheme of acupuncture; develop a COS with TCM characteristics to improve the quality of outcome reporting, This will enable different research data to be summarized and compared, reduce resource waste, and provide more high-quality evidence.